2023
DOI: 10.1038/s41551-023-01050-0
|View full text |Cite
|
Sign up to set email alerts
|

Resolving sepsis-induced immunoparalysis via trained immunity by targeting interleukin-4 to myeloid cells

Abstract: Immunoparalysis is a compensatory and persistent anti-inflammatory response to trauma, sepsis or another serious insult, which increases the risk of opportunistic infections, morbidity and mortality. Here, we show that in cultured primary human monocytes, interleukin-4 (IL4) inhibits acute inflammation, while simultaneously inducing a long-lasting innate immune memory named trained immunity. To take advantage of this paradoxical IL4 feature in vivo, we developed a fusion protein of apolipoprotein A1 (apoA1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Trained immunity improves innate responses to infection and is emerging as a key component of host directed therapies (HDT) and strategies to improve vaccine efficacy and the design of respiratory mucosal vaccines (26,27,(37)(38)(39). Both IFN-γ and IL-4 can induce trained immunity in murine and human macrophages (12,19,40,41). MDM trained with IFN-γ and LPS, and stimulated with Mtb had increased TNF in the acute activation phase of trained immunity (19), which we observed in IFN-γ primed MDM subsequently stimulated with Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…Trained immunity improves innate responses to infection and is emerging as a key component of host directed therapies (HDT) and strategies to improve vaccine efficacy and the design of respiratory mucosal vaccines (26,27,(37)(38)(39). Both IFN-γ and IL-4 can induce trained immunity in murine and human macrophages (12,19,40,41). MDM trained with IFN-γ and LPS, and stimulated with Mtb had increased TNF in the acute activation phase of trained immunity (19), which we observed in IFN-γ primed MDM subsequently stimulated with Mtb.…”
Section: Discussionmentioning
confidence: 99%
“…While sepsis provides a pertinent analog for the systemic endotoxin exposure observed in SAM and a sepsis-like biomarker profile has been described among children recovering from SAM who die after hospital discharge ( 26 , 27 ), only one (0.01%) of our cohort of children with complicated SAM was septic at the time of blood sampling. Thus, improved understanding of how immune adaptations occur could support stratification of patients according to specific immunological risk factors, as has been trialed for immune hyper- versus hyporeactive states in septic patients ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…118 Schrijver et al loaded the fusion protein of apolipoprotein A1 and IL-4 into lipid NPs and found these lipid NPs could overcome immunoparalysis in septic mice. 119 As an early discovered lipid NPs, liposomes were proposed as an effective drug-delivery system. Chen et al suggested that lanosterolcontaining liposomes (LAN-L) had anti-inflammatory effects in sepsis and reduced mortality in septic mice.…”
Section: How Nano-medicinal Materials Can Help Diagnose and Treat Sep...mentioning
confidence: 99%